Mixed neuroendocrine–non-neuroendocrine neoplasms of the gallbladder: a case report - Tatsuki Ishikawa; Katsunori Nakano; Masafumi Osaka; Kenichi Aratani; Kadotani Yayoi; Kiyokazu Akioka; Kuniyuki Tsuchiya; Yohei Hosokawa (Surgical Case Reports)
Abstract Background  Primary neuroendocrine tumors of the gallbladder (GB-NETs) are rare, accounting for 0.5% of all NETs and 2.1% of all gallbladder cancers. Among GB-NETs, mixed neuroendocrine–non-neuroendocrine neoplasms of the gallbladder (GB-MiNENs) are extremely rare. Case presentation We present the case of a 66-year-old woman who was referred to us for the management of a gallbladder tumor (incidentally found during abdominal ultrasonography indicated for gallbladder stones). The patient had no history of abdominal pain or fever, and the findings on a physical examination were unremarkable. Blood tests showed normal levels of tumor markers. Imaging studies revealed a mass of approximately 10 mm in diameter (with no invasion of the gallbladder bed) located at the fundus of the gallbladder. A gallbladder cancer was suspected. Therefore, an open whole-layer cholecystectomy with regional lymph nodes dissection was performed. The postoperative course was uneventful, and she was discharged on postoperative day 6. Pathological findings showed GB-MiNENs with invasion of the subserosal layer and no lymph node invasion (classified T2aN0M0 pStage IIA according to the Union for International Cancer Control, 8th edition staging system). Analysis of the neuroendocrine markers revealed positive chromogranin A and synaptophysin, and a Ki-67 index above 95%. Fourteen months after the operation, a local recurrence was detected, and she was referred to another hospital for chemotherapy. Conclusions  GB-MiNENs are extremely aggressive tumors despite their tumor size. Optimal therapy should be chosen for each patient.